Augmenting E Protein Activity Impairs cDC2 Differentiation at the Pre-cDC Stage - Bajana, Sandra; Thomas, Kevin; Georgescu, Constantin; Zhao, Ying; Wren, Jonathan D.; Kovats, Susan; Sun, Xiao-Hong (Frontiers in Immunology, 2020)
Dendritic cell (DC) specification and differentiation are controlled by a circuit of transcription factors, which regulate the expression of DC effector genes as well as the transcription factors themselves. E proteins are a widely expressed basic helix-loop-helix family of transcription factors whose activity is suppressed by their inhibitors, ID proteins. Loss-of-function studies have demonstrated the essential role of both E and ID proteins in different aspects of DC development. In this study, we employed a gain-of-function approach to illustrate the importance of the temporal control of E protein function in maintaining balanced differentiation of conventional DC (cDC) subsets, cDC1 and cDC2. We expressed an E protein mutant, ET2, which dimerizes with endogenous E proteins to overcome inhibition by ID proteins and activate the transcription of E protein targets. Induction of ET2 expression at the hematopoietic progenitor stage led to a dramatic reduction in cDC2 precursors (pre-cDC2s) with little impact on pre-cDC1s. Consequently, we observed decreased numbers of cDC2s in the spleen and lung, as well as in FLT3L-driven bone marrow-derived DC cultures. Furthermore, in mice bearing ET2, we detected increased expression of the IRF8 transcription factor in cDC2s, in which IRF8 is normally down-regulated and IRF4 up-regulated. This aberrant expression of IRF8 induced by ET2 may contribute to the impairment of cDC2 differentiation. In addition, analyses of the transcriptomes of splenic cDC1s and cDC2s revealed that ET2 expression led to a shift, at least in part, of the transcriptional profile characteristic of cDC2s to that of cDC1. Together, these results suggest that a precise control of E protein activity is crucial for balanced DC differentiation.